Factors affecting the performance of financial sector in Malaysia - Bong, Lie Lin (Universiti Malaysia Sarawak, (UNIMAS), 2012)
This paper is to analyze and detennine the factors that affecting the financial sector perfonnance in Malaysia for the period of five years, from year 2006 to 2011. From the study, the result shows that, the perfonnance of Malaysian financial sector is stable and quite profitable because of systematic Malaysian financial systems regulations and the strong financial capital. However, the global financial crisis occurred during year 2008 to 2009 was affected the financial sector globally and affected the financial institution's service qualit~ The study will use the financial ratios and apply the CAMEL Model namely, Capital adequacy, Asset quality, Management, Earnings, and Liquidity to detennine the factors affecting the financial sector perfonnance. So, in order to identify the detenninants of perfonnance of Malaysian financial sector during 2006 to 2011, this study has chosen mUltiple regression analysis. Besides that, the dependent variables are consisting profitability ratio, which Return on Assets (ROA) and Return on Equity (ROE), then independent variables are the CAMEL Methods. So from the study, the results also shows that, the ROA and ROE are depends on the CAMEL. Lastly, there are a significant relationship between the dependent variables and the independent variables.